(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The mere act of attempting to say something about the social sciencestheir origin, history, development, and destinyis, in itself, an ambitious and excessive endeavor. Who could even produce a state of the art of any of the disciplines or subdisciplines that today fall under that broad label? To say something meaningful in this regard, we would have to rely on the enormous collective efforts that some groups of scholars and certain institutions have undertaken in recent years (Wallerstein, I., 2006; Heilbron, J.; L. Magnusson & B. Wittrock, 1998; Porter, T. and D. Ross, 2003; UNESCO, 2010; UNESCO, 2013).